Short, terminally modified 2′-OMe RNAs as inhibitors of microRNA - Blechinger, Jenny; Pieper, Hanna; Marzenell, Paul; Kovbasyuk, Larisa A.; Serva, Andrius; Starkuviene, Vytaute; Erfle, Holger; Mokhir, Andriy (Chemical Communications, 2013)
We applied 14-mer 2′-OMe RNAs as inhibitors of selected micro RNAs. To improve their properties, we introduced a trimethoxystilbene residue at the 5′-terminus and three 2′-fluoro-2′-deoxynucleotides at the 3′-terminus to obtain potent inhibitors, whose mismatch discrimination is substantially better than that of typically applied >18-mers. © 2013 The Royal Society of Chemistry.